Life expectancy in relation to cardiovascular risk factors: 38 year follow-up of 19 000 men in the Whitehall study - Clarke, R; Emberson, J; Fletcher, A; Breeze, E; Marmot, M; Shipley, M (2009)
Objective: To assess life expectancy in relation to cardiovascular risk factors recorded in middle age. Design: Prospective cohort study. Setting: Men employed in the civil service in London, England. Participants: 18 863 men examined at entry in 1967-70 and followed for 38 years, of whom 13 501 died and 4811 were re-examined in 1997. Main outcome measures: Life expectancy estimated in relation to fifths and dichotomous categories of risk factors (smoking, "low" or "high" blood pressure (≥140 mm Hg), and "low" or "high" cholesterol (≥5 mmol/l)), and a risk score from these risk factors. Results: At entry, 42% of the men were current smokers, 39% had high blood pressure, and 51% had high cholesterol. At the re-examination, about two thirds of the previously "current" smokers had quit smoking shortly after entry and the mean differences in levels of those with high and low levels of blood pressure and cholesterol were attenuated by two thirds. Compared with men without any baseline risk factors, the presence of all three risk factors at entry was associated with a 10 year shorter life expectancy from age 50 (23.7 v 33.3 years). Compared with men in the lowest 5% of a risk score based on smoking, diabetes, employment grade, and continuous levels of blood pressure, cholesterol concentration, and body mass index (BMI), men in the highest 5% had a 15 year shorter life expectancy from age 50 (20.2 v 35. 4 years). Conclusion: Despite substantial changes in these risk factors over time, baseline differences in risk factors were associated with 10 to 15 year shorter life expectancy from age 50.